Analysis of a City’s Heat Island Effect on the Micro-Climate Parameters within Cities - Rishabh Sharma; Khan Amadur Rahman; Vasyl Tyshchenko; Oksana Illiash; Iryna Mezentseva (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
The Urban Heat Island (UHI) is a micro-climatic phenomenon that influences the urban areas by elevating its temperature. UHI not only causes the thermal discomfort but also exert serious health issues along with aggravation of urban microclimate. Although a lot of research has been done on this phenomenon but UHI effect on micro scale is still less explored. This paper attempts to make a contribution in UHI studies of micro-climate. It consists of examination of UHI impact on microclimate of Aligarh city areas using mobile traverse method. This study determined the presence and extent of UHI’s microclimate variation within urban communities of different environmental layout and functional uses. The UHI effect started to appear from early afternoon and continue to rise with maximum UHI intensity recorded at early night. The highest recorded UHI intensity was 3.1 °C (at 21:00 hrs.), and the lowest was 0.6 °C (at 09:00 hrs.). A comparison of two districts of the same city located at a distance of 3 km and differing in population density, the number of buildings and landscaping showed that in the L1 area with more dense population and low landscaping, the temperature was consistently higher during the daily period; also the L1 region had less humidity, which combined with the already high temperature, makes it difficult to breathe and control the microclimate. These findings can be used for consideration for the future sustainable development of the affected area in regard of thermal comfort, environmental health and urban planning.